The road to European Economic and Monetary Union - Helmut Schlesinger (Intereconomics, 1991)
The debate on the concrete shape of the second stage of European economic and monetary union ist in full swing. What are the benefits that may be expected from EMU? What risks have to be avoided?
Keywords: 330; European Community